Strategi adaptasi keluarga pekerja industri garmen di Kabupaten Bogor pada situasi pandemi COVID-19 - Luh Kitty Katherina; Angga Siska Rahadian; Puguh Prasetyoputra; Andhika Ajie Baskoro (Jurnal Kependudukan Indonesia, 2021)
Before the COVID-19 pandemic, the garment sector had the best performance globally, especially in Asia. In Indonesia, the industry provides employment, especially for women. However, the pandemic adversely impacted the garment industry and its workers. This paper aims to explore the adaptation strategies carried out by families of garment workers by employing a subset of the 2021 Family and Community Resilience Survey by the Research Center for Population, Indonesian Institute of Sciences (LIPI). The subsample comprises 100 families of garment industry workers residing in Bogor Regency. The results suggest that 89% of respondents stated that they were experiencing economic problems due to the pandemic. Moreover, these workers are vulnerable due to their employment status, predominantly contract and non-routine employees (26%) and they do not have savings and assets. Several activities were reported as part of their adaptive strategies in coping with economic stressors, namely changing their lifestyle (77.5%), changing family consumption (58%), and seeking loans from relatives (55%). Furthermore, 90% of workers reported not receiving salary subsidy programs. Therefore, the government needs to pay more attention to workers who are vulnerable to being heavily affected by the pandemic and should incorporate these findings in future social protection programs.